Pain Susceptibility Phenotypes in Those Free of Knee Pain With or at Risk of Knee Osteoarthritis: The Multicenter Osteoarthritis Study. Issue 4 (7th February 2019) - Carlesso, Lisa C.; Segal, Neil A.; Frey‐Law, Laura; Zhang, Yuqing; Na, Lu; Nevitt, Michael; Lewis, Core E.; Neogi, Tuhina
Abstract : Objective: It is not clear why some individuals develop pain with knee osteoarthritis (OA). We undertook this study to identify pain susceptibility phenotypes (PSPs) and their relationship to incident persistent knee pain (PKP) 2 years later. Methods: We identified individuals free of PKP from the Multicenter Osteoarthritis Study, a longitudinal cohort of older adults with or at risk of knee OA. Latent class analysis was used to determine PSPs that may contribute to development of PKP apart from structural pathology. These included widespread pain, poor sleep, and psychological factors as well as pressure pain threshold and temporal summation (TS) as determined by quantitative sensory testing (QST). We used logistic regression to evaluate the association of sociodemographic factors with PSPs and the relationship of PSPs to the development of PKP over 2 years. Results: A total of 852 participants were included (mean age 67 years, body mass index 29.5 kg/m 2, 55% women). Four PSPs were identified, primarily characterized by varying proportions (low/absent, moderate, or high) of the presence of pressure pain sensitivity and of facilitated TS, reflecting different measures of sensitization. Subjects in the PSP with a high proportion of pressure pain sensitivity and a moderate proportion of facilitated TS were twice as likely to develop incident PKP over 2 years (odds ratio 1.98 [95% confidence interval 1.07–3.68]) compared with subjects in the PSP having a low proportion of sensitization by both measures. Conclusion: Four PSPs were identified, 3 of which were predominated by QST evidence of sensitization and 1 of which was associated with developing PKP 2 years later. Prevention or amelioration of sensitization may be a novel approach to preventing onset of PKP in OA.